1971
DOI: 10.1677/joe.0.0510333
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Oestrogen and Progesterone in the Plasma of Non-Pregnant, Pregnant and Lactating Guinea-Pigs

Abstract: SUMMARY A competitive protein-binding assay of progesterone and a radioimmunoassay of total unconjugated oestrogens were evaluated and employed in the measurement of these steroids in the plasma of guinea-pigs at different times during the reproductive cycle. Production rates (PR) were calculated from the product of the endogenous steroid concentration and its metabolic clearance rate. During the oestrous cycle, plasma progesterone levels rose from undetectable levels at the time of ovulation to 2·8 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
121
6

Year Published

1973
1973
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(144 citation statements)
references
References 2 publications
17
121
6
Order By: Relevance
“…Opening of the membrane precedes oestrus, but its timing is too variable to be used in accurately establishing the onset of oestrus (Sisk 1976). The monophasic cyclic fluctuations of P 4 , coincident with the ovarian luteal phase (dioestrus, lack of sexual behaviour) found in the current study are in accordance with the data of others (Challis et al 1971;Garris et al 1984), whereas the E 2 levels in the current study did not show cyclic fluctuation which is in agreement with the non-cyclic fluctuation reported by Croix and Franchimont (1975). These data run counter to previous findings of Hutz et al (1990) who describe a biphasic follicular growth associated with biphasic E 2 production.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Opening of the membrane precedes oestrus, but its timing is too variable to be used in accurately establishing the onset of oestrus (Sisk 1976). The monophasic cyclic fluctuations of P 4 , coincident with the ovarian luteal phase (dioestrus, lack of sexual behaviour) found in the current study are in accordance with the data of others (Challis et al 1971;Garris et al 1984), whereas the E 2 levels in the current study did not show cyclic fluctuation which is in agreement with the non-cyclic fluctuation reported by Croix and Franchimont (1975). These data run counter to previous findings of Hutz et al (1990) who describe a biphasic follicular growth associated with biphasic E 2 production.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, it has been shown that there is a significant elevation of plasma progesterone (P 4 ) coincident with the luteal phase (dioestrus) in guinea pigs (Feder et al 1968;Challis et al 1971;Blatchley et al 1976;Garis and Foreman 1984), whereas fluctuations of plasma oestradiol (E 2 ) levels occur throughout the oestrous cycle (Chalis et al 1971;Croix and Franchimont 1975;Garris and Foreman 1984;Westfahl and Vekasy 1988;Hutz et al 1990).…”
mentioning
confidence: 99%
“…The progesterone levels in G. musteloides present many interesting points when compared to those of the laboratory guinea-pig as reported by Challis, Heap & Illingworth (1971). The patterns of change in plasma progesterone levels during gestation appear to be similar in the two species-relatively low concentrations are found during the first 15 days, highest levels are found at mid-pregnancy, and then somewhat lowered but yet sustained high levels are found at 51 to 60 days in the guinea-pig and 41 to 50 days in G. musteloides (Text-fig.…”
Section: Animals and Sample Collectionmentioning
confidence: 72%
“…(2) The highest progesterone concentration found in the plasma of the guinea-pig and cuis during pregnancy is certainly very much higher than those found in many other animals such as the pregnant hamster (25 ng/ml; Leavitt & Blaha, 1970), ewe (15 to 20 ng/ml; Bassett, Oxborrow, Smith & Thorburn, 1969;Fylling, 1970) and cow (8 ng/ml; Donaldson, Bassett & Thorburn, 1970). Thus, not to mention the high level of 513 ng/ml, even the progesterone concentrations (6-3 to 15 ng/ml) during the first 15 days in guinea-pigs Challis et al, 1971) and in G. musteloides (23 to 60 ng/ml) are, in fact, high levels and the progesterone requirement during the first 15 days' gestation in both species of cavy is, therefore, by no means low compared to these animals.…”
Section: Animals and Sample Collectionmentioning
confidence: 92%
See 1 more Smart Citation